KERJASAMA INDONESIA - UNAIDS (UNITED NATIONS PROGRAMME ON HIV AND AIDS) DALAM PENANGANAN HIV/ADS DI PROVINSI RIAU - Rivano, Andre; ", Afrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research describes the cooperation between Indonesia and UNAIDS in handling HIV and AIDS in Riau Province. Handling the HIV / AIDS problem requires the involvement of international organizations to work together with the government so that the handling of this epidemic can be carried out quickly, broadly and in a coordinated manner. United Nations Program on HIV and AIDS or UNAIDS is an IGO which is the main supporter of global action against the HIV epidemic. In Indonesia, HIV AIDS was first discovered in Bali Province in 1987. Until now, HIV AIDS has spread in 407 out of 507 districts / cities or can be said to reach 80 percent of all provinces in Indonesia. In this paper the authors use two theories, namely policy theory and role theory, these theories are considered suitable to explain the response of the Riau government in responding to the cooperation between Indonesia and UNAIDS in dealing with HIV / AIDS in Riau Province.The results of this study found that policies for handling and preventing HIV / AIDS in Indonesia prioritized adolescents, support for high-risk groups, prevention of mother-to-child transmission, then prioritized care and provided important and accurate information through the mass media. In handling HIV / AIDS cases in Riau Province, the Riau Provincial Government has implemented its policy through Riau Province Regional Regulation Number 4 of 2006 concerning HIV / AIDS Prevention and Control. One of the policies of Riau Province in dealing with HIV / AIDS in its region as recommended by UNAIDS is Preventive Treatment with Isoniazid for HIV or PLWHA. Preventive treatment with Isoniazid for HIV or PLWHA is one of the important health interventions for TB prevention in HIV and has been recommended since 1998 by WHO and the Join United Nations Program on HIV / AIDS (UNAIDS). Keywords: Cooperation, Unaids, HIV, AIDS,